Immune Dysregulation, Polyendocrinopathy, Enteropathy, X-Linked Syndrome: A Paradigm of Immunodeficiency with Autoimmunity - Barzaghi, Federica; Passerini, Laura; Bacchetta, Rosa (Frontiers in Immunology, 2012)
Immune dysregulation, Polyendocrinopathy, Enteropathy, X-linked (IPEX) syndrome is a rare monogenic primary immunodeficiency (PID) due to mutations of FOXP3, a key transcription factor for naturally occurring (n) regulatory T (Treg) cells. The dysfunction of Treg cells is the main pathogenic event leading to the multi-organ autoimmunity that characterizes IPEX syndrome, a paradigm of genetically determined PID with autoimmunity. IPEX has a severe early onset and can become rapidly fatal within the first year of life regardless of the type and site of the mutation. The initial presenting symptoms are severe enteritis and/or type 1 diabetes mellitus, alone or in combination with eczema and elevated serum IgE. Other autoimmune symptoms, such as hypothyroidism, cytopenia, hepatitis, nephropathy, arthritis, and alopecia, can develop in patients who survive the initial acute phase. The current therapeutic options for IPEX patients are limited. Supportive and replacement therapies combined with pharmacological immunosuppression are required to control symptoms at onset. However, these procedures can allow only a reduction of the clinical manifestations without a permanent control of the disease. The only known effective cure for IPEX syndrome is haematopoietic stem cell transplantation, but it is always limited by the availability of a suitable donor and the lack of specific guidelines for bone marrow transplant in the context of this disease. This review aims to summarize the clinical histories and genomic mutations of the IPEX patients described in the literature to date. We will focus on the clinical and immunological features that allow differential diagnosis of IPEX syndrome and distinguish it from other PID with autoimmunity. The efficacy of the current therapies will be reviewed, and possible innovative approaches, based on the latest highlights of the pathogenesis to treat this severe primary autoimmune disease of childhood, will be discussed.